The Power of Music An Exploration of the Evidence - Hallam, Susan (Open Book Publishers, 2022)
Building on her earlier work, 'The Power of Music: A Research Synthesis of the Impact of Actively Making Music on the Intellectual, Social and Personal Development of Children and Young People', this volume by Susan Hallam and Evangelos Himonides is an important new resource in the field of music education, practice, and psychology. A well-signposted text with helpful subheadings, 'The Power of Music: An Exploration of the Evidence' gathers and synthesises research in neuroscience, psychology, and education to develop our understanding of the effects of listening to and actively making music. Its chapters address music's relationship with literacy and numeracy, transferable skills, its impact on social cohesion and personal wellbeing, as well as the roles that music plays in our everyday lives. Considering evidence from large population samples to individual case studies and across age groups, the authors also pose important methodological questions to the research community. 'The Power of Music' defends qualitative research against a requirement for randomised control trials that can obscure the diverse and often fraught contexts in which people of all ages and backgrounds are exposed to, and engage with, music. This magnificent and comprehensive volume allows the evidence about the power of music to speak for itself, thus providing an essential directory for those researching music education and its social, personal, and cognitive impact across human ages and experiences.